A Simple, Analytically Solvable, Chamberlinian Agglomeration Model - Michael Pflüger (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
This paper presents a simple Chamberlinian agglomeration model which, like the canonical core-periphery (CP) model, contains two agglomerative forces. However, in contrast to that model, the present model is analytically solvable. Moreover, the present model exhibits a 'supercritical pitchfork bifurcation' rather than the 'subcritical pitchfork bifurcation' of the CP model. This may be a better description for some agglomerative processes than the 'catastrophic' emergence of complete agglomeration predicted by the CP model.
Keywords: 330; Regionale Konzentration; Kern-Peripherie-Beziehung; Aussenwirtschaftstheorie; Neue ökonomische Geographie; Mark-up Pricing; Internationale Arbeitsmobilität; Humankapital; Dynamisches Gleichgewicht; Theorie